Nanopore Characteristics of the Cambrian Niutitang Formation Organic-Rich Shales in the Middle Yangtze Region and Its Formation Controlling Factors - Jie Xu; Weihua Guo; Bin Yang; Dongxu Ma; Li Zhao; Haotian Liu; Hongjie Ji; Huifei Tao (Geofluids)
The shale of Cambrian Niutitang Formation is one of the most important shale gas reservoirs in the Middle Yangtze region, South China. Nanopores are important reservoir spaces for shale gas. The study of pore characteristics and its formation controlling factors is of great significance for the exploration and development of shale gas in the Niutitang Formation. In this study, two drilling core samples and two profile samples were investigated. The laser Raman, X-ray diffraction analysis, FE-SEM, and low-pressure N2 and CO2 adsorption methods are used to study the geochemical and mineral compositions of the shales, and the nanopore characteristics and its formation controlling factors of the shales are discussed. Results show that the shales have the following features: (1) rich in organic matter (OM) and the total organic carbon (TOC) contents ranging from 2.65 to 11.33%, with an average value of 6.81%. (2) The main mineral components of these shales are quartz, feldspar, clay minerals, calcite, and a small amount of pyrite. (3) The samples from the center of the Middle Yangtze region (EY1 well and BGP profile) have a higher maturity value (RmcR0%=4.0%) relatively to the samples from the south of the Middle Yangtze region (XD1 well and JF profile), where the RmcR0% is 2.8%. (4) The maximum N2 adsorption capacity of the four groups of shale samples ranges from 5.090 to 27.333 cm3/g, with an average value of 15.571 cm3/g, while the maximum CO2 adsorption capacity ranges from 2.686 to 5.567 cm3/g, with an average value of 3.776 cm3/g. The higher maturity leads to the EY1 well having the lowest average maximum N2 adsorption capacity, while most of the OM pores in the EY1 well and BGP profile samples are smaller than 10 nm in diameter. The tectonic uplift leads to the profile samples having more meso-macropores than the core samples. The dissolution pores and granular mineral support are the key factors for the better pore structure of the high-evolution stage Niutitang Formation shale.